2023
DOI: 10.1039/d2sc05727a
|View full text |Cite
|
Sign up to set email alerts
|

Long-term spatiotemporal and highly specific imaging of the plasma membrane of diverse plant cells using a near-infrared AIE probe

Abstract: Fluorescent probes of plasma membrane are valuable tools to intuitively and clearly visualize plasma membrane and its relating physiological processes in a spatiotemporal manner; however, most existing probes only realized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…40 Attracted by the merits of AIE dyes, some effective small molecular AIE probes that can specifically target the plasma membrane of animal cells have been reported with very few examples on the targeted imaging of the plant cytomembrane. 48,49 However, the high permeability of small molecular AIE probes makes them easy to diffuse into the cytoplasm and then stain organelles with membrane structures (such as endoplasmic reticulum, mitochondrion, and dictyosome), consequently showing inadequate long-time imaging capability for plasma membranes. 34,50−52 The effective design and development of an AIE probe, especially a polymer-based AIE probe, for long-time and targeted imaging of the plant cytomembrane still remain very challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Attracted by the merits of AIE dyes, some effective small molecular AIE probes that can specifically target the plasma membrane of animal cells have been reported with very few examples on the targeted imaging of the plant cytomembrane. 48,49 However, the high permeability of small molecular AIE probes makes them easy to diffuse into the cytoplasm and then stain organelles with membrane structures (such as endoplasmic reticulum, mitochondrion, and dictyosome), consequently showing inadequate long-time imaging capability for plasma membranes. 34,50−52 The effective design and development of an AIE probe, especially a polymer-based AIE probe, for long-time and targeted imaging of the plant cytomembrane still remain very challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As summarized in Figure 4d,f, under the optimal staining time or dosage, the value of imaging integrity can reach 100%, demonstrating the excellent cytomembrane imaging ability of P6. Moreover, the proportion of the fluorescent region to the total cell region (S imaging ) 48 was calculated to be 20.3% and 21.9% respectively under the optimal staining time and optimal dosage (Figure 4g,h). Above the optimal staining time and dosage, the values of S imaging changed little, which further demonstrated that P6 is capable of selectively and completely staining the cytomembrane rather than staining other regions of onion epidermal cells.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 For this purpose, our group proposed an antipermeable strategy to design a series of AIE-active probes. 24,25 These probes showed high contrast and long-term imaging ability for plasma membranes and have general universality for diverse plant cells. However, their AIE nature and relatively low solubility in aqueous solution make them to easily aggregate inside cell walls, leading to undesirable specificity for the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent wheat germ agglutinin (WGA) conjugates have been recently proposed for staining the cell membrane via binding to glycosyls on the cell surface; nevertheless, this kind of macromolecular WGA conjugate also shows strong affinity for the Golgi apparatus with abundant glycosyls . To overcome these problems, great efforts have been made to develop selective and efficient cell membrane probes. For instance, Collot and co-workers created a new family of cyanine-based amphiphilic MemBright probes, which exhibited selective and homogeneous membrane staining with high contrast and were successfully used in super-resolution imaging; Klymchenko et al developed B-2AZ as a selective cell membrane probe and employed it in 3D imaging to reveal fine intercellular tunneling nanotubes . In addition, a purine-based probe was proposed for imaging the cell membrane of neurons .…”
Section: Introductionmentioning
confidence: 99%